Plasma and semen antioxidant responses of West African Dwarf goats to Parquetina nigrescens leaf extract administration - Ndubuisi-Ogbonna, Lois Chidinma; Akintunde, Adeyinka Oye; Noibi, Oluwafikunayo Fareed; Oso, Oluwaseyi Emmanuel (Ovozoa: Journal of Animal Reproduction, 2025)
This study investigated the antioxidant responses in both plasma and semen of West African Dwarf (WAD) goats following the administration of Parquetina nigrescens leaf extract (PNLE). Twelve clinically healthy WAD bucks were randomly assigned into two groups, each receiving 0 mL (control), and 4 mL of PNLE, respectively, over a 21-day period. Blood and semen samples were collected at baseline and post-treatment to evaluate antioxidant markers including catalase, superoxide dismutase (SOD), malondialdehyde (MDA), total antioxidant capacity (TAC), lipid peroxidation (LP), and glutathione peroxidase (GPx). An antioxidant response was observed. In the control group (0 mL PNLE), significant negative correlations between baseline and post-treatment values—particularly B-Cat. vs. SOD (r= -0.973), B-Cat. vs. MDA (r= -0.990), and B-MDA vs. SOD (r= -0.999)—suggested impaired endogenous antioxidant regulation.  Conversely, administration of 4 mL PNLE significantly enhanced antioxidant status, with strong positive correlations among key indices, notably catalase vs. GPx (r= 0.960**) and TAC vs. SOD (r= 0.999**), reflecting improved systemic antioxidant synergy. Semen antioxidant profiles also showed better enzymatic coordination and reduced lipid peroxidation, indicating the extract’s potential to alleviate reproductive oxidative stress. Overall, Parquetina nigrescens (P. nigrescens) demonstrated marked antioxidative efficacy, supporting both systemic and reproductive redox balance in WAD goats. P. nigrescens leaf extract enhances seminal antioxidant status in WAD goats, thereby promoting reproductive and systemic health. This study recommends its inclusion as a phytogenic additive in goat production, especially in breeding programs prone to oxidative stress.